Acute Efavirenz Intoxication in a 16-year-old HIV Negative Girl: A Case Report and Literature Review - Minoo Moghimi; Zahra Nekoukar; Navid Khosravi (Pharmaceutical and Biomedical Research, 2024)
Background: There are only rare case reports that revealed the efavirenz (EFV) toxicity. Case Report: This study presents an acute intoxication with 12 g of efavirenz in a 16-year-old healthy girl whose main problem was dose-dependent neurotoxicity. No other serious EFV-related side effects were seen. Previous serious side effects of EFV were observed in HIV-infected patients who underwent long-term combination drug therapy. Conclusion: Accordingly, in terms of the key clinical messages, serious adverse effects of efavirenz are expected to be observed in long-term use in combination with other antiretroviral drugs.